2023
DOI: 10.1073/pnas.2217276120
|View full text |Cite
|
Sign up to set email alerts
|

Resurrection genomics provides molecular and phenotypic evidence of rapid adaptation to salinization in a keystone aquatic species

Abstract: Ecologists and evolutionary biologists are increasingly cognizant of rapid adaptation in wild populations. Rapid adaptation to anthropogenic environmental change is critical for maintaining biodiversity and ecosystems services into the future. Anthropogenic salinization of freshwater ecosystems is quickly emerging as a primary threat, which is well documented in the northern temperate ecoregion. Specifically, many northern temperate lakes have undergone extensive salinization because of urbanization and the as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 91 publications
1
12
0
Order By: Relevance
“…The method of Santiago et al (2020) has now been applied to different species, particularly in the last year, including insects, such as honeybees (Sang et al, 2022); birds, such as Black Robin (von Seth et al, 2022); fishes, such as turbot, seabream and seabass (Saura et al, 2021), Baltic herring (Atmore et al, 2022), pikeperch (De Los Ríos-Pérez et al, 2022, coho salmon (Martinez et al, 2022), catfish (Coimbra et al, 2023) and sailfish (Ferrette et al, 2023); wild mammals, such as grey wolf (Pacheco et al, 2022), killer whales (Kardos et al, 2023), sika deer (Iijima et al, 2023), scimitar-horned oryx (Humble et al, 2023) and gorilla (Alvarez-Estape et al, 2023); humans (Bird et al, 2023); domestic species, such as pigs (Krupa et al, 2022), cattle (Jin et al, 2022;Magnier et al, 2022), sheep (Djokic et al, 2023;Drzaic et al, 2022), horse (Criscione et al, 2022) and chicken (Gao et al, 2023;Liu et al, 2023); plants, such as walnut (Ding et al, 2022); crustaceans, such as Daphnia (Wersebe & Weider, 2023) and fungi (Singh et al, 2021). As suggested by Santiago et al (2020), the method is generally reliable for about 200 generations in the past, although…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method of Santiago et al (2020) has now been applied to different species, particularly in the last year, including insects, such as honeybees (Sang et al, 2022); birds, such as Black Robin (von Seth et al, 2022); fishes, such as turbot, seabream and seabass (Saura et al, 2021), Baltic herring (Atmore et al, 2022), pikeperch (De Los Ríos-Pérez et al, 2022, coho salmon (Martinez et al, 2022), catfish (Coimbra et al, 2023) and sailfish (Ferrette et al, 2023); wild mammals, such as grey wolf (Pacheco et al, 2022), killer whales (Kardos et al, 2023), sika deer (Iijima et al, 2023), scimitar-horned oryx (Humble et al, 2023) and gorilla (Alvarez-Estape et al, 2023); humans (Bird et al, 2023); domestic species, such as pigs (Krupa et al, 2022), cattle (Jin et al, 2022;Magnier et al, 2022), sheep (Djokic et al, 2023;Drzaic et al, 2022), horse (Criscione et al, 2022) and chicken (Gao et al, 2023;Liu et al, 2023); plants, such as walnut (Ding et al, 2022); crustaceans, such as Daphnia (Wersebe & Weider, 2023) and fungi (Singh et al, 2021). As suggested by Santiago et al (2020), the method is generally reliable for about 200 generations in the past, although…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Reid and Pinsky (2022) showed that the method exhibits ≥90% accuracy for detecting fast severe declines in population size, outperforming other methods. The method has also been applied to different sets of data from different species (Atmore et al, 2022;Bird et al, 2023;Ding et al, 2022;Ferrette et al, 2023;Pacheco et al, 2022;von Seth et al, 2022;Wersebe & Weider, 2023). However, the simulation tests have always a restricted scope, as the models simulated cannot encompass all the complexities of real genomes.…”
mentioning
confidence: 99%
“…We assumed that the postglacial expansions from multiple glacial refuges in the temperate Palearctic, together with southward migration during the LGM, produced the present wide distribution of Clade B of D. galeata . However, rapid evolutionary responses by cladocerans (Geerts et al, 2015; Wersebe & Weider, 2023) might mean that thermal preferences and other properties of past Daphnia populations were very different from those of today (on which we based our models). This could obviously introduce substantial error into inferences of past distribution based on present‐day ENMs (Pearman et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…populations inhabiting large permanent lakes offer considerable opportunities here, as their resting eggs can remain preserved in undisturbed sediments for up to 200 years. With enough sampling from sediment cores with stable stratigraphies, population-level studies might be extended over time periods exceeding several hundreds of generations (RoyChowdhury et al 2015;Yousey et al 2018; Chatuvedi et al 2021; Isanti-Navarro et al 2021;Wersebe et al 2023).…”
mentioning
confidence: 99%